2017
DOI: 10.12991/mpj.2017.32
|View full text |Cite
|
Sign up to set email alerts
|

Development of a validated high-performance liquid chromatographic method for the determination of Lurasidone in pharmaceuticals

Abstract: A new, rapid and simple HPLC method for determination of Lurasidone in its tablets has been developed and validated. Lurasidone and internal standard (Chlorpromazine) was separated on a Zorbax XDB C8 column (4.6 x 50 mm, 3.5 µm particle size) set at 40°C and quantified by ultraviolet detection at 230 nm. The mobile phase was phosphate buffer (pH:3, 20 mM): acetonitrile: methanol (55:10:35, v/v/v) with a flow rate of 1.2 mL/min. Retention times of Chlorpromazine and Lurasidone was 4.73 and 6.89 minutes, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…A reliable and accurate method is critical for PK/toxicokinetic studies and the evaluation of parameters like C max , T max , and area under the curve (AUC). Only a few methods are currently available for determining the concentration of LUR in plasma/serum/blood (Atila Karaca & Yeniceli, 2017; Chae et al, 2012; Katteboina et al, 2016; Koo et al, 2011; Patteet et al, 2014, 2015). A comparative study of published methods (refer to Table 1) indicated that two methods for quantitation of LUR from rat plasma reported by Koo et al (2011) and Chae et al (2012) have longer run time of 4.0 and 8.0 min, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…A reliable and accurate method is critical for PK/toxicokinetic studies and the evaluation of parameters like C max , T max , and area under the curve (AUC). Only a few methods are currently available for determining the concentration of LUR in plasma/serum/blood (Atila Karaca & Yeniceli, 2017; Chae et al, 2012; Katteboina et al, 2016; Koo et al, 2011; Patteet et al, 2014, 2015). A comparative study of published methods (refer to Table 1) indicated that two methods for quantitation of LUR from rat plasma reported by Koo et al (2011) and Chae et al (2012) have longer run time of 4.0 and 8.0 min, respectively.…”
Section: Introductionmentioning
confidence: 99%